Desain E-LKPD Berbasis Concept Image Siswa pada Materi Barisan dan Deret - Dita Oktavihari; Junaidi Junaidi; Gilang Primajati; M. Gunawan Supiarmo; Eka Kurniawan (Griya Journal of Mathematics Education and Application, 2026)
This study aims to develop a concept image-based E-LKPD on sequences and series using the ADDIE model.This development research was carried out up to the Development stage, which includes Analysis, Design,and Development. In the analysis stage, learning needs were identified through concept image tests,interviews, and documentation studies. The results of the analysis showed that students still had difficultyin understanding the concepts of sequences and series in depth, differentiating the concepts of sequences andseries, and connecting various mathematical representations. Based on these needs, an E-LKPD was designedthat included problem-oriented activities, pattern exploration, concept construction, concept reflection, andcontextual application. In the development stage, the E-LKPD prototype was compiled and validated bymaterial experts and media experts to assess the feasibility of content, presentation, language, andappearance. The validation results showed that the developed E-LKPD met the valid criteria and was suitablefor use as a supporting teaching material for mathematics learning. The concept image-based E-LKPD isexpected to help students build a better conceptual understanding of sequences and series through theintegration of visual, verbal, numeric, and symbolic representations.